KANDUNGAN SERAT, ANTOSIANIN, DAN SIFAT ORGANOLEPTIK PRODUK DESSERT BOX BERBASIS UBI UNGU DAN BERAS HITAM - Risa Rahmawati; Nitta Isdiany; Pusparini Pusparini; Putu Bunga Fitridewi (Jurnal Gizi dan Dietetik, 2025)
The prevalence of diabetes mellitus in 2023 increased to 11.7% from 10.9% in 2019. This was caused by changes in dietary patterns in the community, such as the consumption of high sugar and energy foods. Therefore, snack need to be modified so that they can meet the recommendation of diabetes mellitus diet, which is high in fiber and contains antioxidants. Black rice and purple sweet potatoes are local foods that are high in fiber and anthocyanins. The purpose of this study was to determine the effect of different proportions of black rice and purple sweet potatoes on organoleptic properties, nutritional content, dietary fiber, and anthocyanins. The study design was experimental. The research methods used were hedonic test for organoleptic properties, proximate test for macro-nutrient content, by difference for energy content, enzymatic-gravimetry for dietary fiber, and pH differential spectrophotometry for anthocyanins. The main research was conducted in September-October 2025 at the Food Technology Laboratory (ITP) Poltekkes Kemenkes Bandung, Food Technology Laboratory of Universitas Pasundan, and BBSPJIA. The ratio for purple sweet potato flour and black rice flour were F1 (60%:40%), F2 (70%:30%), and F3 (80%:20%). F3 was the best formula based on the organoleptic test results. There were significant differences in taste and overall aspects between the F1 and F3 and the F2 and F3. F3 contain 162.4 calories, 32.36 grams of carbohydrates, 4.28 grams of protein, 1.76 grams of fat, 3.69 grams of dietary fiber, and 0.94 mg of anthocyanin per serving. The production cost is Rp9.866 and selling price is Rp14.799.